1991
DOI: 10.1139/b91-274
|View full text |Cite
|
Sign up to set email alerts
|

The number and distribution of incompatibility factors in natural populations of Pleurotus ostreatus and Pleurotus sapidus

Abstract: A. S. and SCHWANDT, J. W. 1991. The number and distribution of incompatibility factors in natural populations of Pleurotus ostreatus and Pleurotus sapidus. Can. J. Bot. 69 : 2187-2191.Pairings of single-spore isolates from different basidiocarps were made to examine the numbers and distributions of incompatibility factors in the tetrapolar basidiomycetes Pleurotus ostreatus and Pleurotus sapidus. These factors do not appear to be randomly distributed, with multiple basidiocarps on a single tree or log arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Multiple mating alleles have been observed in several basidiomycete populations (e.g. Anderson et al 1991, Kay & Vilgalys 1992. In the tetrapolar Pleurotus ostreatus a tendency towards spatial clustering of mating alleles (A and B) was observed (Anderson et al 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Multiple mating alleles have been observed in several basidiomycete populations (e.g. Anderson et al 1991, Kay & Vilgalys 1992. In the tetrapolar Pleurotus ostreatus a tendency towards spatial clustering of mating alleles (A and B) was observed (Anderson et al 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Mushrooms in the genus Pleurotus appear to deviate slightly from this pattern. Mating-type surveys of the two species P. populinus and P. pulmonarius (first reported as P. ostreatus and P. sapidus, respectively [see Anderson et al, 1973;Vilgalys et al, 1993]), revealed consistently more B alleles than A alleles (126 A and 354 B alleles estimated for P. populinus and 30 A and 90 B alleles estimated for P. pulmonarius [Anderson et al, 1991]). An additional unique property of the Pleurotus A mating-type is that with only a single exception, there has been no demonstration of intra-A mating-type recombination in P. spondoleucus, P. ostreatus, and P. djamor (Larraya et al, 1999;Liou, 2000;Takemaru, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Kummer is an excellent edible mushroom widely cultivated in many countries of the world. As in most hymenomycetes, the mating system of this fungus, leading to the formation of a dikaryon that can differentiate to produce fruiting bodies, is known to be bifactorial heterothallism (tetrapolality) controlled by two unlinked multialletic factors, A and B (Terakawa 1960;Eguenio and Anderson 1968;Anderson et al 1991).…”
Section: Introductionmentioning
confidence: 99%